Microparticles formed during storage of red blood cell units support thrombin generation. Issue 4 (April 2018) - Bouchard, Beth A.; Orfeo, Thomas; Keith, Hollis N.; Lavoie, Elizabeth M.; Gissel, Matthew; Fung, Mark; Mann, Kenneth G.
Abstract : BACKGROUND: Intact red blood cells (RBCs) appear to support thrombin generation in in vitro models of blood coagulation. During storage of RBC units, biochemical, structural, and physiological changes occur including alterations to RBC membranes and release of microparticles, which are collectively known as storage lesion. The clinical consequences of microparticle formation in RBC units are unclear. This study was performed to assess thrombin generation via the prothrombinase complex by washed RBCs and RBC-derived microparticles as a function of RBC unit age. METHODS: Well-characterized kinetic and flow cytometric assays were used to quantify and characterize microparticles isolated from leukocyte-reduced RBC units during storage for 42 days under standard blood banking conditions. RESULTS: Stored RBCs exhibited known features of storage lesion including decreasing pH, cell lysis, and release of microparticles demonstrated by scanning electron microscopy. The rate of thrombin formation by RBC units linearly increased during storage, with the microparticle fraction accounting for approximately 70% of the prothrombinase activity after 35 days. High-resolution flow cytometric analyses of microparticle isolates identified phosphatidylserine-positive RBC-derived microparticles; however, their numbers over time did not correlate with thrombin formation in that fraction. CONCLUSION: Red blood cell-derived microparticles capable of supporting prothrombinase function accumulate during storage, suggesting an increased potential of transfused units as they age to interact in unplanned ways with ongoing hemostatic processes in injured individuals, especially given the standard blood bank practice of using the oldest units available. Abstract : Supplemental digital content is available in the text.